Splenic Transcriptional Responses in Severe Visceral Leishmaniasis: Impaired Leukocyte Chemotaxis and Cell Cycle Arrest - de Melo, Caroline Vilas Boas; Guimarães Torres, Felipe; Hermida, Micely D’El-Rei; Fontes, Jonathan L. M.; Mesquita, Bianca Ramos; Brito, Reginaldo; Ramos, Pablo Ivan P.; Fernandes, Gabriel R.; Freitas, Luiz Antônio Rodrigues; Khouri, Ricardo; Costa, Carlos Henrique Nery; dos-Santos, Washington L. C. (Frontiers in Immunology, 2021)
Structural changes in the spleen have been reported in several infectious diseases. In visceral leishmaniasis (VL), a severe parasitic disease caused by Leishmania spp., the loss of white pulp accompanies a severe clinical presentation. Hamster model reproduces aspects of human VL progression. In the early stages, a transcriptomic signature of leukocyte recruitment was associated with white pulp hyperplasia. Subsequently, impaired leukocyte chemotaxis with loss of T lymphocytes in the periarteriolar lymphoid sheath occurred. This differential gene expression was subsequently corroborated by transcriptomic profiling of spleens in severe human VL. At the latest stage, spleen disorganization was associated with increasing clinical signs of VL. White pulp disruption was accompanied by decreased DLK1 expression. The expression of CXCL13, CCR5, CCL19, CCR6, CCR7 and LTA decreased, likely regulated by CDKN2A overexpression. Our findings enlighten a pathway implying cell cycle arrest and decreased gene expression involved in spleen organization.